Komunikasi Etis dalam Pendidikan Kristen di Tengah Relativisme Moral di Era Digitalisasi - Andreas Kurniawan; Tjutjun Setiawan; Suranto Suranto; Simon Simon (Sekolah Tinggi Teologi Berea, Salatiga, 2026)
This article focuses on explaining explaining how ethical communication relates to Christian Religious Education amidst the emergence of moral relativism in the digitalization era. The available discussion tends to focus more on Christian Religious Education (CRE) in relation to spirituality, ethics, or evangelical values. Given the still-limited direction of studies that elaborate on communication in Christian Religious Education (CRE) amidst moral relativism, the researcher sees this as a gap in the discussion. The method used by the researcher in elaborating this paper is descriptive-analytical qualitative. The selection of this method is to obtain a deep and comprehensive understanding of phenomena that are conceptual in nature. The findings of this study indicate that moral relativism is becoming increasingly dominant as exposure to diverse values and norms through digital media increases. As a result, cyberbullying and hate speech in digital media have become dominant. The collaborative efforts of the church, school, and family become crucial in building ethical communication rooted in Christian values.ABSTRAKArtikel ini berfokus menguraikan bagaimana komunikasi Etis dalam kaitan Pendidikan Agama Kristen ditengah menguaknya relativisme moral dalam era digitalisasi. Kajian ini peneliti uraikan karena observasi terkait penelitian yang berkaitan topik ini masih amat minim dibahas. Kecenderungan arah pembahasan yang tersedia lebih mentik-beratkan PAK dalam kaitan spiritual, etika maupun nilai-nilai Injili. Dari masih minimnya arah kajian yang mengelaborasikan tentang komunikasi dalam PAK ditengah relativisme moral, peneliti melihat hal ini sebagai gap dalam pembahasan. Metode yang digunakan peneliti dalam menguraikan tulisan ini kualitatif deskriptif-analitis. Pemilihan metode ini untuk memperoleh pemahaman mendalam dan komprehensif terhadap fenomena yang bersifat konseptual. Temuan kajian ini mengemukakan relativisme moral menjadi semakin dominan seiring dengan meningkatnya paparan terhadap keragaman nilai dan norma melalui media digital. Akibatnya, perundungan di media seperti bullyan, ujan kebencian mendominasi. Upaya kolaborasi gereja, sekolah, dan keluarga menjadi sangat krusial dalam membangun komunikasi etis yang berakar pada nilai-nilai Kristiani. Kata Kunci: Komunikasi, Pendidikan Agama Kristen, Moral, Digitalisasi.